Concurrent influence of top-down and bottom-up inputs on correlated activity of Macaque extrastriate neurons - Yaser Merrikhi (Nature Portfolio, 2018)
Changes in correlated activity of neurons are believed to influence their information coding capacity. Here, the authors show how top-down and bottom-up inputs and their interaction differentially alter the correlated activity of neurons in extrastriate cortex